Social media use among young people in China: a systematic literature review - Lian, Tang; Omar, Siti Zobidah; Mohd Zawawi, Julia Wirza; Bolong, Jusang (Sage Publications, 2021)
The widespread use of social media has promoted extensive academic research on this channel. The present study conducts a systematic analysis of extant research on social media use among young people in China. This systematic literature review aims to identify and bridge gaps in topics, theories, variables, and conceptual frameworks in studies of social media usage among young people in China. The study aims to develop a cause–effect framework that shows the causal relationships among research structures. The PRISMA method is used to review 20 articles drawn from the Scopus and Google Scholar databases. From the analysis, 10 major research topics, eight theories or models, and a complete framework of causal relations emerge. It is recommended that future research on social media should include a greater diversity of types of social media, investigate a wider range of research topics, and adopt different theories or models. Researchers should also implement a more complete and detailed systematic method for reviewing literature on social media research in China.